Android Based Student Information System - Chavan, HS; Chavan, AA; Karangutkar, SV; Melasagare, SM (International Journal of Computer Sciences and Engineering, 2020)
In today's world, everything is dependent on technology. From small to large work, we use technology. But still in some school and colleges, the attendance is taken on paper or sheets. Also other information related to students or teachers are stored taken on papers. This is very tedious job. Also lots of time get wasted due to these activities. So there can be risk of information loss. Hence this is also need to be updated with the technology. So it will be helpful for schools and colleges to maintain the records. So "Android Based Student Information System" can store student information and also used for marking students attendance. It has three modules namely Admin, Teacher and Student. So this can be very effective for teachers. The overhead can be reduced from the teachers as they need not have to waste their time by taking the attendance on paper or storing the information related to student on paper. Also it will give the students, the information about themselves. So this will be useful application for both teachers and students.